Mobility issues among the elderly in Kota Kinabalu, Sabah: an initial study - Harifah Mohd Noor; Adilah Md Ramli; Jurry Foo; Mohd Azizul Ladin; Mazdi Marzuki; Chai, Ai Jing (UMT Press, 2024)
Ageing has become an issue of concern in developing countries such as Malaysia. Senior citizens are still able to contribute to employment, albeit with mobility demands. The purpose of this study is to explore mobility issues among the elderly. This study used a mixed-method approach. Purposive sampling survey forms were delivered to 644 people aged 60 years and above. The study interviewed three informants to support the research’s findings. Data analysis used descriptive and inferential approaches such as percentages, mean scores and cross-tabulation. The results revealed that health had become a major mobility issue. Their limited access to public transport and unfamiliarity with Information and Communication Technology (ICT) has limited their choices of transportation such as e-hailing services. Most have strong support from their families or children to reach their destinations. However, not all elderly have access to a private car and do not live with children or other family members. The challenge is to improve public transit and enhance ICT usage to meet the mobility needs of the elderly. The findings can be utilised to generate ideas for local authorities and various agencies to develop policies and strategies to satisfy the mobility needs of the elderly.